The Ambulatory Integration of the Medical and Social (AIMS) model: A retrospective evaluation. (27th May 2016) - Rowe, Jeannine M.; Rizzo, Victoria M.; Shier Kricke, Gayle; Krajci, Kate; Rodriguez-Morales, Grisel; Newman, Michelle; Golden, Robyn
ABSTRACT: An exploratory, retrospective evaluation of Ambulatory Integration of the Medical and Social (AIMS), a care coordination model designed to integrate medical and non-medical needs of patients and delivered exclusively by social workers was conducted to examine mean utilization of costly health care services for older adult patients. Results reveal mean utilization of 30-day hospital readmissions, emergency department (ED) visits, and hospital admissions are significantly lower for the study sample compared to the larger patient population. Comparisons with national population statistics reveal significantly lower mean utilization of 30-day admissions and ED visits for the study sample. The findings offer preliminary support regarding the value of AIMS.